Comparative study of bacteria and biofertilizer on strawberry fruit quality grown in perlite substrate - Durdigul Botirova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Strawberries are widely consumed fruits known for their rich nutritional content and desirable sensory attributes. Enhancing their quality in soilless cultivation systems, such as perlite substrates, is crucial for sustainable and efficient production. This study evaluated the comparative effects of a humic substance-based biofertilizer (Khumic 100) and the plant growth-promoting bacterium Pantoea agglomerans on the growth and fruit quality of strawberries grown in perlite under controlled greenhouse conditions. Treatments included Khumic-100, Pantoea agglomerans (INB-22), and a non-treated control group. Key parameters assessed were plant height, leaf area, flowering and fruiting patterns, and average fruit weight. The Khumic-100 treatment resulted in the highest fruit weight, along with the most vigorous vegetative and reproductive development. The bacterial treatment showed moderate improvements compared to the control. These results suggest that Khumic-100 is more effective in enhancing strawberry plant performance and fruit quality in perlite-based cultivation systems.